(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Three different types of Ti6Al4V powders produced by Electrode Induction melting Gas Atomization (EIGAed), Plasma Rotating Electrode Process (PREPed) and Plasma Atomization (PAed), were compared in terms of particle shape and particle size distribution (PSD) using particle size and shape analyzer 500 NanoXY. Results showed that the particle size distribution of these Ti6Al4V powders were bimodal. The Roundness and Elongation of the most analyzed Ti6Al4V powders were more than 80%, and the average Bluntness index were 75%, 85%, and 96%, respectively; there were 52%, 81%, and 93% Ti6Al4V powders without satellite, respectively; which indicated that EIGAed, PRERed, and PAed powders had good sphericity and low content of satellites. The microstructure of the Ti6Al4V powders was composed of martensite α′.